PENGARUH PEMBERIAN SIRUP BELIMBING WULUH DENGAN PENAMBAHAN EKSTRAK KAYU SECANG TERHADAP KADAR GLUKOSA DARAH POST PRANDIAL PADA SUBJEK DEWASA SEHAT - Nuzulia Hasna (2022)
Averrhoa bilimbi syrup with caesalpinia sappan wood extract addition is an alternative drink that has been formulated and has a high flavonoid content so that it is believed to reduce blood glucose levels in healthy adult subjects. This study used an experimental study design method with 11 healthy adults as subjects. There were two groups in this study, namely the control group which was only given pure glucose solution and the treatment group which was given an averrhoa bilimbi syrup drink with addition of caesalpinia sappan wood extract which had been added with pure glucose. The results of the intervention showed that the mean postprandial blood glucose levels in the intervention group were lower than the control group. The results of the AUC area paired t-test showed that the intervention group was significantly different (p<0.05) compared to the control group. The results of the calculation of %PKGD were 35,55%. Thus, it can be concluded that giving averrhoa bilimbi syrup drink with addition of caesalpinia sappan wood extract can help reduce post prandial blood glucose levels in healthy adult subjects.